Profile of plants for poisoning cases in human Alagoas state / Perfil dos casos de intoxicação por plantas em humanos no estado de Alagoas - Eládia Maria Santos; Katiane Melo Gomes; Lucas Pedrosa Souto Maior; Lyvia Quintela Cavalcante Trajano; Saskya Araújo Fonseca; Thiago José Matos-Rocha; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2019)
Toxic plants are so named because they have bioavailable substances capable of causing metabolic abnormalities such changes are recognized as symptoms of intoxication. The objective of this paper is to provide comparative data to tables of plant poisoning in the state of Alagoas. The study is a retrospective observational study based on the collection of Database Information on Disease Notification System of Alagoas state the period from January 2010 to July 2014 Most reported cases of plant poisoning in humans in state of Alagoas occurred in 2010, and the city of Arapiraca presented the highest percentage of cases and the plant Nicotiana tabacum (tobacco / smoke) was most notified. The most affected age group was 1-9 years and 20-34 years. It was concluded that the shortage in the collection of epidemiological data and the lack of laboratory research contribute to lack of information about this type of poisoning, especially in humans.